Parametric Adjustments to the Rankine Vortex Wind Model for Gulf of Mexico Hurricanes - Jeong, Chan K; Panchang, Vijay; Demirbilek, Zeki (2012)
Parametric wind models are often used to reconstruct hurricane wind fields from a limited set of hurricane parameters. Application of the Rankine Vortex and other models used in forecasting Gulf of Mexico hurricanes show considerable differences between the resulting wind speeds and data. The differences are used to guide the development of adjustment factors to improve the wind fields resulting from the Rankine Vortex model. The corrected model shows a significant improvement in the shape, size, and wind speed contours for 14 out of 17 hurricanes examined. The effect on wave fields resulting from the original and modified wind fields are on the order of 4 m, which is important for the estimation of extreme wave statistics. Published in the Journal of Offshore Mechanics and Arctic Engineering, v134, Nov 2012. Prepared in cooperation with Dockwise USA, Houston, TX and the Maritime Systems Engineering Department, Texas A&M University, Galveston. Sponsored in part by USACE Navigation System (NavSys), Flood and Coastal Storm Damage Reduction, and Dredging Operations and Environmental Research (DOER).